Spatial pattern of literacy in Baitarani basin, Odisha - Panda, Siva Prasad; Sethy, Kabir Mohan; Tripathy, S. N. (National Geographical Journal of India, 2022)
Literacy has traditionally been described as the ability to read and write a simple message with understanding in any language. Literacy in any area was determined largely by a variety of historical, social and economic factors. Literacy brings about fundamental changes in socio-economic development. The disparity in literacy generates several social, economic and political problems, which may threaten the foundation of development. Literacy and education are necessary for human development. It contributes to better income and health of the population. The national adult Education Programme launched countrywide in 1978 has viewed literacy as a means to bring about a fundamental change in socio-economic development. Literacy and education attainment is the key variables inuencing fertility, mortality and migration. Therefore, literacy is the decisive factor for the development and population control as well as inequality in literacy tends to lead to several socio-economic problems, which in turn gives rise to regional imbalance. The disparity in literacy generates several social, economic and political problems, which may threaten the foundation of development. The main objective of the present study is to analyze the pattern of literacy and changes in the Baitarani basin, Odisha.